PERBEDAAN EARNINGS MANAGEMENTBERDASARKAN UKURAN PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Fensy Oktavia Komala (Jurnal Riset Akuntansi dan Keuangan, 2010)
The purpose of this reseacrh is to investigate Earnings management differences accross companies according to its size. Previous researches show company size tend to affect earnings management behavior. Sample are collected from companies listed on Indonesian Stock Exchange year over 2003-2009. Using Chi-Square Test, the result shows that statistically there is no differences of Earnings management magnitude between small, medium and large companies. Keywords:  Earnings Management, Discretionary Accruals, Non Discretionary Acruals, Total Accruals.